ANALISIS PENGARUH SELF EFFICACY, KAPABILITAS DAN PERILAKU KERJA INOVATIF TERHADAP KINERJA PEGAWAI SATUAN POLISI PAMONG PRAJA KABUPATEN ROKAN HULU - Abdul Khadir (Program Studi Manajemen Universitas Pasir Pengaraian, 2020)
This study aims to determine the effect of self-efficacy, capabilities and innovative work behavior simultaneously on the performance of Rokan Hulu Regency Civil Service Police Unit, both partially and simultaneously. The population in this study were employees of the Civil Service Police Unit Rokan Hulu Regency. The research sample used accidental sampling techniques as many as 79 people. Data collection methods using observations, questionnaires and documents. Data analysis using multiple linear regression analysis using the SPSS program. Obtained a self-efficacy t-test 64,759, capability 10.246 and innovative work behavior 0.202. Simultaneously, the results F-count of 2491,716. The results showed that 90% of employee performance can be influenced by variables of self efficacy, capabilities and innovative work behavior, while the remaining 1% is influenced by other variables not examined in this study. The conclusion of this study parially only self efficacy and capability variables that have positive and significant effect on employee performance, while simultaneously self efficacy variables, capabilities and innovative work behavior have a positive and significant effect on employee performance.